Pengaruh Phubbing terhadap Minat Belajar IPS Siswa Kelas IX SMP di Kota Bandung - Silmia, Ashiila Zalfa; Salira, Ade Budhi; Holilah, Mina (Peneliti.net, 2024)
After the Covid-19 pandemic some time ago, it had a major impact on human life in the world, including in education, one of which is the progress of using the internet in online learning through smartphones. This progress also brings convenience to build communication and show their identity to others so that individuals feel comfortable spending long periods of time using smartphones thus unwittingly causing phubbing behavior. This research was conducted to determine the effect of phubbing behavior on students' interest in learning in social studies learning in class IX of SMP BPI 1 Bandung. The approach used is a quantitative approach with survey methods. This research involved 84 students as samples using nonprobability sampling with saturated sampling techniques. The data collection technique used in this research was a questionnaire with scoring using a Likert scale. Hypothesis testing in this research uses simple linear regression analysis. The research results show a sig value. 0.032 < 0.05, then Ho is rejected, Ha is accepted, which means that there is an influence of phubbing behavior on students' interest in learning social studies. Furthermore, researcher obtained a calculated of -2.186, which means that there is an inverse (negative) influence between the two variables. This proves that the lower the phubbing behavior of students, the higher the students' interest in learning social studies.